Cognitive behavioural social skills training: Methods of a randomized controlled trial for youth at risk of psychosis. Issue 6 (4th January 2021) - Addington, Jean; Liu, Lu; Santesteban‐Echarri, Olga; Brummitt, Kali; Braun, Amy; Cadenhead, Kristin S.; Cornblatt, Barbara A.; Holden, Jason L.; Granholm, Eric
Abstract: Aim: Poor functioning has become a hallmark of many youth at clinical high‐risk (CHR) of psychosis. Even for those who do not make the transition to psychosis remain troubled by functional deficits and a decline in functioning increases the odds of transitioning to psychosis. There are very few treatment studies that have attempted to improve social and role functioning. The aim of this paper is to describe the methods of a treatment study to address social and role functioning in CHR. Methods: This was a randomized controlled trial of cognitive‐behavioural social skills training (CBSST) versus a supportive therapy. CBSST combines elements of cognitive behaviour therapy (CBT) and social skills training (SST), two evidence‐based treatments for schizophrenia. By adding CBT to SST to target functioning outcomes, SST can be used to train new social skills, and thoughts that interfere with skilled performance in the real world can be addressed using CBT. We developed an adapted version of CBSST, more appropriate for the age range and illness severity of typical CHR individuals, to attempt to show improvements in social and role functioning for these young people. Results: Two hundred and three participants were recruited for this study. Results include initial baseline data. Conclusion: This article describes the baseline methodology of a CHR youth who have difficulties in social and/or role functioning. It is one of the first clinical trials to address this significant problem.